PENGARUH TEKNOLOGI INFORMASI, KEAHLIAN PEMAKAI DAN INTENSITAS PEMAKAIAN TERHADAP KUALITAS INFORMASI AKUNTANSI PADA PT. BANK RAKYAT INDONESIA (PERSERO), TBK MAKASSAR - Azizah Mirdin, Andi Azzah; Modding, Basri; Mursalim, Mursalim (INVOICE : JURNAL ILMU AKUNTANSI, 2021)
This research is using quantitative study aimed to see the influence of information technologi use, user expertise, and the intensity of usage on the quality of accounting information. The population of this study was PT Bank Rakyat Indonesia (Persero), Tbk, Makassar Branch. The selection of the sample with total sampling methods. The data used in this study of primary data. Data analysis techniques using multiple regression analysis. The results of this study indicate that information technologi use, user expertise, and the intensity of usage have a positive effect and significant on quality of accounting information. Keyword: Information Technologi Use, User Expertise, The Intensity Of Usage, and Quality Of Accounting Information